Hospital-based Phase III Cardiac Rehabilitation Program Improves Low Density Lipoprotein, Triglyceride, and Fasting Blood Glucose Level in Coronary Artery Disease Patients : a 6-month Follow up - Bambang Dwiputra; Fajar Panjaitan; Evan Hindoro; Nurul Fathoni; Anwar Santoso (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
ABSTRACTBackground. Cardiac rehabilitation (CR) has been reported as effective for improving coronary risk factors and increasing exercise tolerance in patients with coronary artery disease (CAD) after cardiac events. It may be performed in 3 stages: acute (phase I), subacute (phase II), and chronic (phase III). In Indonesia, most cardiac rehabilitation programs have been phase I and some phase II, whereas phase III cardiac rehabilitation has not often been performed as it was not covered by national health insurance.Objectives. We assessed the beneficial effects of 6-month hospital-based phase III comprehensive cardiac rehabilitation on physical status and coronary risk factors among CAD patients.Methods. 74 patients were stratified as the intervention group (n=37) and the control group (n=37). In the intervention group, patients participated in hospital-based phase III CR for 6 months, whereas in the control group, they received standard care. CR program consists of warm-up (senam jantung sehat), aerobic exercise, cool-down stretching, and health education session three days a week. Blood glucose and lipid profile examination were performed at the beginning and sixth month to assess patient’s metabolic status.Results. Of 74 patients observed, most patients were male (85.1%) with mean age 54.7+3.4 years old. 57 patients had post-procedural history (77% post-PCI, 4% post-CABG), 8 patients (11%) were still active smokers, 31 patients (42%) had diabetes, and 60 patients (81%) had hypertension. Participation of hospital-based phase III CR program was significantly correlated with lower low-density lipoprotein (LDL) level (p=0.003, r=0,41), triglyceride level (p=0.001, r=0,38), and fasting blood glucose (p<0.001, r=0,46) during 6-month follow up.Conclusion. Patients with CAD who underwent hospital-based phase III CR program had significantly better fasting glucose control, LDL, and triglyceride level during 6-month follow up. These results may encourage other hospitals to perform the same program achieving better prognosis of CAD patients.Keywords: cardiac rehabilitation, high density lipoprotein, low density lipoprotein, triglyceride, blood glucose